The advancing multiculturalism in the German language area and the influence of globalization and migration on the common or colloquial German - Rajchelt, Balbina (Migracja w języku, literaturze i kulturze, 2020)
Germany is undoubtedly a country heavily influenced by migration. The now approximately 20 million inhabitants with a migration background make the German language area a melting pot of different cultures and languages. This leads to a rapid development and adaptation of the German language to these new conditions; and nowhere are these changes more visible than in the common language used in everyday situations.The article deals with the development of colloquial German language over the past few decades, especially in regard to how it has changed due to the steadily growing number of migrants from other language areas. Certain trends in linguistic development are presented using examples of various expressions and phrases that have established themselves in modern German through the influence of other languages and cultures. Migration-related changes in the German grammar are also presented and explained.Furthermore, the influence of globalization on the common and colloquial German language is presented and analysed using short examples.Ultimately, based on the examples and trends presented, a forecast for the possible future development of the colloquial and inevitably also of the general German language is created and the question is answered whether these changes are beneficial to its linguistic development or rather harmful and whether it is worthwhile and even possible to try to counteract them.